Corridors ferroviaires Europe – Asie et coopération internationale :quelles perspectives de développement ? - Joël Forthoffer (Bulletin de l’Association de Géographes Français)
International trade is experiencing strong growth, particularly driven by Asian countries. Europe-Asia trade is carried out mainly by sea. Indeed, despite the rediscovery in recent years of major land routes such as the Trans-Siberian Corridor, international rail freight transport now accounts for only a small proportion of the volumes transported. Can rail infrastructure investments for new corridors in Eurasian space, interoperability and harmonization efforts by intergovernmental organisations and the railway cooperation agencies strengthen the competitiveness of rail transport ?